Evaluation of field grown potato lines transgenic for a cry1Ac9 gene conferring resistance to potato tuber moth - Davidson, M.M.; Takla, M.F.G.; Reader, J.K.; Butler, R.C.; Wratten, S.D.; Conner, A.J. (New Zealand Plant Protection, 2002)
Phthorimaea operculella (Zeller) potato tuber moth (PTM) is an important pest of potatoes The larvae of this insect are difficult to control with insecticides because they mine into foliage and tubers Seven potato cultivars were genetically engineered with a Bacillus thuringiensis cry1Ac9 gene to confer resistance to PTM larvae Fiftysix transgenic lines were established in the field at Lincoln Canterbury as small plots of 10 plants along with replicate control plots of the same but nontransgenic cultivars Fortyfour of the transgenic lines were phenotypically normal Foliage excised from these plants was challenged with PTM larvae in the laboratory All but one line inhibited larval growth compared to nontransgenic plants (Plt;005) For transgenic plants the growth indices of larvae fed fieldgrown foliage were similar to those fed greenhousegrown foliage Thirteen of the 43 resistant lines inhibited larval growth by 8805;40 and produced tuber yields comparable to the nontransgenic plants